molecular biological analysis of hydrocarbon degraders from oily waste polluted sites - Nordin, Noor Faizul Hadry; Merican, Amir Feisal (Penerbit Universiti Sains Malaysia, 2004)
Oily waste has been identified to be the major pollutant in the environment. The sources may come from palm oil mills, refineries, oleo chemical plants, food and beverage industries and also petrochemical industries. Application of physicochemical methods in clean up process do not completely destroy the contamination and costly. These physicochemical technologies are often inadequate because they require the collection and concentration of the pollutants, which is in many instances is dispersed in the environment. Natural treatment utilizing microorganism as degrader or accumulator is currently receiving much favorable attention as a promoting method because microorganisms can take over in situ mineralization of pollutants.